Channeling for everyone a safe, step-by-step guide to developing your intuition and psychic awareness - Neate, Tony (Piatkus, 1997)
Channelling is a skill which everyone can learn and benefit from. It is an extension of your awareness, allowing you first to become aware of your intuitive self and later to become sensitive to subtler levels of consciousness. It can be used both to enhance your creativity and intuition and to channel philosophical teachings. Tony Neate's handbook will guide you safely, step-by-step through the knowledge and understanding necessary for inner development. He provides exercises to help you to prepare to channel and then to take the first steps into channelling. You will gradually discover your own ability to 'let go', allowing wider states of consciousness to become part of your everyday life. You will find new levels of creativity and experience balance, harmony and spiritual growth. Tony Neate writes with wisdom and integrity. He shows how channelling is an empowering way to accelerate your spiritual growth and to improve the quality of your life.